Inflation in macroeconomic terms - Dubiel, Nina; Łomozik, Jakub (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The modern economy, which dynamically responds to both internal and global changes, is exposed to fluctuations in the level of inflation, which have a significant impact on monetary policy, the stability of financial markets and consumer behavior. Understanding this phenomenon and the ability to analyze its effects are therefore becoming indispensable not only for economists, but also for every citizen operating in the realities of a market economy. The results provided important information on how respondents felt about further price increases, which may be useful for further analyses and practical recommendations. The first part of the article discusses the concept of inflation, and the next part discusses the research results.